Antecedents and Consequences of Employee Engagement - Rahayu Utaminingsih; Ratno Purnomo (Jurnal Akuntansi, Manajemen dan Ekonomi, 2017)
This research is a study of the antecedents and consequences of employee engagement that is focused on the sample which is a generation Y. This study was conducted on operational employees working in the field of hospitality. This study takes the title: "Antecedents and consequences of employee engagement (sample on generation Y hospitality employees)". This research is an associative modeled study that investigates the causal relationship with quantitative approach. The population in this study is all hotel employees who work on five hotels listed. The number of respondents taken in this research is 130 respondents. and using questionnaires to obtained the data. Respondents from this study are workers who work in the operational section who have jobs to serve hotel visitors directly. Purposive sampling method is used in the determination of respondents. Based on the results of research and data analysis using multiple regression analysis and simple regression analysis showed that: (1) Perceived Organizational Support has a positive effect on Employee Engagement, (2) Organizational Justice has a positive effect on Employee Engagement, (3) Employee Engagement has a positive effect on Job Satisfaction , (4) Employee Engagement has a positive effect on Job Performance.